2009
DOI: 10.1577/t08-067.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Predation on Galaxiids and Other Native Organisms by Introduced Rainbow Trout in an Ultraoligotrophic Lake in Northern Patagonia, Argentina: A Bioenergetics Modeling Approach

Abstract: Exotic rainbow trout Oncorhynchus mykiss support an economically valuable recreational fishery in Patagonia but also create concern for impacts on native organisms. These concerns are intensified by the possibility of hatchery release programs in this region. We estimated losses of different prey from predation by rainbow trout in Lake Moreno, Río Negro Province, Argentina, using a bioenergetics model combined with input data from directed sampling on growth, seasonal diet, distribution, and thermal experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 36 publications
4
53
0
Order By: Relevance
“…The presence-absence catch data (Table 1) showed that all species described for the Moreno system (Vigliano et al, 2009) were caught in our sampling, except O. hatcheri. This species appears to use only the shallow littoral zone (0-3 m) with high macrophyte vegetation cover (Vigliano et al, 2009), and is thus excluded from hydroacoustic surveys.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The presence-absence catch data (Table 1) showed that all species described for the Moreno system (Vigliano et al, 2009) were caught in our sampling, except O. hatcheri. This species appears to use only the shallow littoral zone (0-3 m) with high macrophyte vegetation cover (Vigliano et al, 2009), and is thus excluded from hydroacoustic surveys.…”
Section: Discussionmentioning
confidence: 88%
“…This species appears to use only the shallow littoral zone (0-3 m) with high macrophyte vegetation cover (Vigliano et al, 2009), and is thus excluded from hydroacoustic surveys. The small number of O. viedmensis caught were always in close association with the near-shore lake bottom and were thus masked within the bottom hydroacoustic signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of resident salmonid populations on receiving freshwater communities have been studied in some depth in places around the world (McDowall 2006), including Patagonia (Aigo et al 2008;Vigliano et al 2009). Much less is known about the ecological effects of anadromous salmonids in marine habitats in general, and no information is available for populations inhabiting the southwestern Atlantic Ocean.…”
mentioning
confidence: 99%
“…This tool has been used to evaluate conservation and management questions regarding factors limiting the production of fish populations (Hartman and Margraf 1993), including the effects of nonnative species (Ruzycki et al 2003;Vigliano et al 2009). Because these models are based on energy balance equations, they are frequently used to estimate consumption or growth for fish while accounting for changes in body mass, thermal experience, diet, and energy density of prey (Chipps and Wahl 2008) and are less time consuming than traditional methods.…”
mentioning
confidence: 99%